Maps for Psychoanalytic Exploration. - Talamo, Parthenope Bion (Karnac Books, 2015)
Maps for Psychoanalytic Exploration brings together Parthenope Bion Talamo's main works, until now published only in Italian. They are made available to a wider readership in this volume through a translation into English by Shaun Whiteside, supported by the generosity of the members of the Melanie Klein Trust. In these chapters Parthenope explores important implications of her father's ideas at different levels of psychic and social organisation. Her writing is very clear and, as Dr Anna Bauzzi, the Editor of the Italian edition, writes in her Introduction, the quality of it makes many of Bion's ideas more accessible, without any reduction of their complexity.